In-silico docking based design and synthesis of [1H,3H] imidazo[4,5-b] pyridines as lumazine synthase inhibitors for their effective antimicrobial activity - Sunil L Harer; Manish S Bhatia (Wolters Kluwer Medknow Publications, 2014)
Purpose: The imidazopyridine moiety is important pharmacophore that has proven to be useful for a number of biologically relevant targets, also reported to display antibacterial, antifungal, antiviral properties. Riboflavin biosynthesis involving catalytic step of Lumazine synthase is absent in animals and human, but present in microorganism, one of marked advantage of this study. Still, this path is not exploited as antiinfective target. Here, we proposed different interactions between [1H,3H] imidazo[4,5-b] pyridine test ligands and target protein Lumazine synthase (protein Data Bank 2C92), one-step synthesis of title compounds and further evaluation of them for in vitro antimicrobial activity. Materials and Methods: Active pocket of the target protein involved in the interaction with the test ligands molecules was found using Biopredicta tools in VLifeMDS 4.3 Suite. In-silico docking suggests H-bonding, hydrophobic interaction, charge interaction, aromatic interaction, and Vanderwaal forces responsible for stabilizing enzyme-inhibitor complex. Disc diffusion assay method was used for in vitro antimicrobial screening. Results and Discussion: Investigation of possible interaction between test ligands and target lumazine synthase of Mycobacterium tuberculosis suggested 1i and 2f as best fit candidates showing hydrogen bonding, hydrophobic, aromatic and Vanderwaal's forces. Among all derivatives 1g, 1j, 1k, 1l, 2a, 2c, 2d, 2e, 2h, and 2j exhibited potent activities against bacteria and fungi compared to the standard Ciprofloxacin and Fluconazole, respectively. The superiority of 1H imidazo [4,5-b] pyridine compounds having R' = Cl >No 2 > NH 2 at the phenyl/aliphatic moiety resident on the imidazopyridine, whereas leading 3H imidazo[4,5-b] pyridine compounds containing R/Ar = Cl > No 2 > NH 2> OCH 3 substituents on the 2 nd position of imidazole.